Impact of Parental Psychological Control on Adolescent Anxiety: Mediated by Self-Esteem among Adolescents - Altaf, Zohra; Khattak, Aftab Khan; Riaz, Atika (Annals of Human and Social Sciences, 2025)
The purpose of this study was to examine the mediating effect of self-esteem on the relationship between parental psychological control and adolescent anxiety. Participants included 320 adolescents who completed self-report measures with established reliability and validity to examine their perceptions of parental psychological control, self-esteem, and anxiety. Mediation analysis found that parental psychological control was significantly positively related to anxiety, and self-esteem acted as a significant mediator of this relation. Based on a multiple mediation analysis, parental psychological control was associated with lower levels of self-esteem, which were subsequently linked to higher GI anxiety. The indirect effect was statistically significant, indicating significant mediation. Overall, this study suggests that self-esteem is an essential psychological mechanism by which controlling parenting styles may influence adolescent mental health. The results have important implications on the need to focus on supportive parenting practices, as well as improving adolescent self-esteem to mitigate anxiety. Recommendations includes that future interventions incorporate parental psycho-education and adolescent self-esteem enhancement to reduce anxiety outcomes.